MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG PENJUMLAHAN DAN PENGURANGAN MELALUI MEDIA PENGGARIS BAGI ANAK TUNAGRAHITA RINGAN - Junaidi - As (Universitas Negeri Padang, 2013)
This research aim to to: 1) describe the learning process of media use a ruler in learning addition and subtraction up to 30, and 2) Prove that if a ruler media can improve learning outcomes mathematical addition and subtraction up to 30 for children in mental retardation were D.3 Class SLB Center Payakumbuh. The results showed that 1) the learning process of addition and subtraction by using the ruler done in two cycles. First cycle with seven meetings and the second cycle with eight meetings. Each cycle begins with the planning, implementation (initial activity, core and end), observation, and analysis and reflection. 2) Learning outcomes seen no increase in capacity addition and subtraction by using the ruler children. It is evident from the study of children: when asessmen children only scored one (1). After being given a lesson to the media a ruler in the first cycle of learning outcomes of children to the sum to 30 for the ID and the RN has a maximum value (10) and FR with a value of (9). Cycle II learning subtraction with media ID ruler scored (9), Rn and FR earned value (8) of the 10 questions adds a one-time saving techniques tested. Thus, it can be suggested at the school, teachers and researchers can use the media next to a ruler in addition and subtraction up to 30.